“Nivel de autoestima y tipo de violencia familiar en estudiantes del nivel secundario de las instituciones educativas: Túpac Amaru y Angel Custodio Garcia Ramirez. Distrito de Tarapoto, Octubre Diciembre 2011” - Mayta Clausner, Alan José (2011)
Bearing diverse manifestations of violence in mind in such teenagers as low academic performance, coyness, aggressiveness, pandillaje, etc. lt decided to research was investigation with the fundamental aim to describe the types of family violence and his relation with the level of autoesteem which affect the students and our locality. There executed a study of investigation of descriptive level correlaciona! of quantitative type with a qualitative approach, where the population was shaped by 31 O students from 12 to 15 years of the 1 º and 2 º degree of the l.E Túpac Amaru and Angels Custodio García Ramirez October - December, 2011. The incident went to 99 % of highly significant confidence and of 0.01 %, focusing the study in: level of autoesteem, types of familiar violence, age, sex and if these have relation with the autoesteem of the students. The results showed the presence of manifestations of psychological violence with 88.3 % of both sexes and in the group etáreo of 13 - 14 years the relevant more, with a predominance of the psychological modality on the physics, turning out to be in addition manifestations, of low autoesteem with 38.3 %, being the total registered in both lnstitutions and being reflected in the aggressiveness and in the coyness which are symptoms more associated with the mistreatment and 20.0 % it demonstrates to be submitted to sexual violence being this the minimal percentage. These results demonstrate the need of an investigation to major depth that allows to know the magnitude of VI this problem in the different lnstitutions of our locality, it will use as base to design strategies of intervention in the community with intersectorial participation. To establish educational permanent programs to early ages, to anticipate the family violence and the low level of autoesteem in the students, with the aim to eliminate or reduce these manifestations that so much affect the teenagers and the rest of the family.